The Effect of Organizational Citizenship Behavior and Burnout on Organizational Variable in Bank Indonesia Representatif Office Pematangsiantar - Sabaruddin Dermawan; Sri Rahayu (CV. Doki Course and Training, 2026)
This study aims to explore how Organizational Citizenship Behavior and burnout influence work quality, with organizational commitment as an intermediary variable at the Bank Indonesia Representative Office in Pematangsiantar . Quantitative methods were used in this study, employing survey techniques. Information was collected using questionnaires distributed to staff at the Bank Indonesia Representative Office in Pematangsiantar and analyzed using Partial Least Squares ( SmartPLS )-based Structural Equation Modeling (SEM). The results indicate that Organizational Citizenship Behavior positively and significantly influences organizational commitment and work quality. Conversely, burnout negatively and significantly influences organizational commitment but does not show a significant direct effect on work quality. Furthermore, organizational commitment positively and significantly influences work quality. The indirect effect analysis highlights that burnout negatively and significantly affects work quality through organizational commitment, while Organizational Citizenship Behavior does not significantly affect work quality through organizational commitment. These results indicate that organizational commitment acts as an intermediary variable in the relationship between burnout and work quality, but does not mediate the relationship between Organizational Citizenship Behavior and work quality. This study aims to provide theoretical contributions to the field of human resource management and practical guidance for the Bank Indonesia Representative Office in Pematangsiantar in improving employee work quality by managing burnout, enhancing Organizational Citizenship Behavior, and fostering organizational commitment.